Phosphor powder, wavelength converter and light-emitting device

By adopting a phosphor powder of a specific composition, the problem of the phosphor powder in the prior art being prone to deterioration under a high temperature environment is solved, and the wavelength conversion of less heat deterioration and efficient blue light to infrared light is achieved.

CN116917439BActive Publication Date: 2025-04-25DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280017924.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-02
Filing Date
2022-02-25
Publication Date
2025-04-25
Estimated Expiration
2042-02-25

AI Technical Summary

Technical Problem

The existing phosphor powder is prone to deterioration due to heat in a high temperature environment, and cannot effectively convert blue light into infrared light.

Method used

The phosphor powder of the general formula (Eu(1-x)(1-z)M1xM2(1-x)z)2(Si1-yAly)5N8) is adopted, wherein M1 contains at least La, M2 contains at least Ba, x is 0.005-0.2, y is 0-0.1, z is greater than 0.44 and is less than 0.99 to suppress thermal deterioration and thermal extinction.

Benefits of technology

It realizes that the phosphor powder is not easily deteriorated due to heat, maintains the luminous intensity in high temperature environments, and is suitable for use with severe temperature changes, such as vehicle-mounted uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116917439B_ABST
    Figure CN116917439B_ABST
Patent Text Reader

Abstract

The present invention relates to a phosphor powder, which contains a phosphor represented by the following general formula (I). In the general formula (I), M1 contains at least La, and may further contain one or more elements selected from lanthanide elements other than Y and La, M2 contains at least Ba, and may further contain one or more elements selected from Mg, Ca and Sr, x is 0.005 to 0.2, y is 0 to 0.1, and z is greater than 0.44 and less than 0.99. (Eu (1-x)(1-z) M1 x M2 (1-x)z )2(Si 1-y Al y )5N8···(I).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to phosphor powder, a wavelength converter and a light-emitting device, and more specifically to phosphor powder capable of emitting infrared light, a wavelength converter containing the phosphor powder, and a light-emitting device having the wavelength converter. Background Art

[0002] So far, various phosphors have been developed for use in light-emitting devices, such as phosphors for white LEDs, that can convert blue light into "visible light" with a longer wavelength than blue light, such as red light. On the other hand, for industrial use, there is also a demand for phosphors that can convert blue light into infrared light (near infrared light) with a wavelength exceeding 700nm.

[0003] Claim 13 of Patent Document 1 describes a near-infrared phosphor having a composition represented by the following formula (I).

[0004] Li a Sr b La c Si d N e Eu f ···(I)

[0005] (a~f are numbers satisfying a+b+c+d+e+f=100, 0≤a≤8.22, 0.22≤b≤17.33, 1.12≤c≤11.36, 22.41≤d≤38.09, 49.47≤e≤56.09, 0.88≤f≤1.01.)

[0006] Patent Document 2 describes a phosphor that contains at least Eu, at least one element selected from Al, Y, La, and Gd, Si, and N, and emits light with a wavelength of 760 nm or more when irradiated with ultraviolet light or visible light. Specifically, Example 35 of the document describes a phosphor that contains Eu, Ba, La, Si, and N as constituent elements.

[0007] In Non-Patent Document 1, for a 2-x Si 5 N 8 :Eu x The reason why the phosphor having the composition shown is degraded by heat was examined.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2019 / 240150

[0011] Patent Document 2: International Publication No. 2020 / 203234

[0012] Non-patent literature

[0013] Non-patent literature 1: J. Am. Chem. Soc. 2012, 134, 14108-14117 Summary of the invention

[0014] From the viewpoint of extending the life of a light-emitting device and improving reliability, it is important to make the phosphor less likely to deteriorate due to heat.

[0015] The present inventors have conducted various studies with the aim of obtaining phosphor powder that is less likely to deteriorate due to heat, and specifically, with the aim of obtaining phosphor powder that is less likely to deteriorate due to heat and can convert blue light into infrared light (near infrared light).

[0016] The present inventors have completed the invention provided below after conducting research.

[0017] According to the present invention, the following phosphor powder can be provided.

[0018] The present invention relates to a phosphor powder containing a phosphor represented by the following general formula (I).

[0019] (Eu (1-x)(1-z) M1 x M2 (1-x)z ) 2 (Si 1-y Al y ) 5 N 8 ···(I)

[0020] In the general formula (I),

[0021] M1 contains at least La, and may further contain one or more elements selected from lanthanoid elements other than Y and La.

[0022] M2 contains at least Ba, and may further contain one or more elements selected from Mg, Ca and Sr.

[0023] x is 0.005 to 0.2,

[0024] y is 0 to 0.1,

[0025] z is greater than 0.44 and less than or equal to 0.99.

[0026] In addition, according to the present invention,

[0027] A wavelength converter can be provided, which contains the above-mentioned phosphor powder.

[0028] In addition, according to the present invention,

[0029] A light-emitting device can be provided, which includes the above-mentioned wavelength converter.

[0030] According to the present invention, it is possible to provide a phosphor powder that is not easily degraded by heat. Specifically, according to the present invention, it is possible to provide a phosphor powder that is not easily degraded by heat and can convert blue light into infrared light (near infrared light). BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the X-ray diffraction pattern of the phosphor powder obtained in the example. DETAILED DESCRIPTION

[0032] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0033] The drawings are for illustration purposes only, and the present invention should not be interpreted in a restrictive manner by the drawings.

[0034] <Phosphor powder>

[0035] The phosphor powder of the present embodiment contains a phosphor represented by the following general formula (I).

[0036] (Eu (1-x)(1-z) M1 x M2 (1-x)z ) 2 (Si 1-y Al y ) 5 N 8 ···(I)

[0037] In the general formula (I),

[0038] M1 contains at least La, and may further contain one or more elements selected from lanthanoid elements other than Y and La.

[0039] M2 contains at least Ba, and may further contain one or more elements selected from Mg, Ca and Sr.

[0040] x is 0.005 to 0.2,

[0041] y is 0 to 0.1,

[0042] z is greater than 0.44 and less than or equal to 0.99.

[0043] The phosphor powder of this embodiment is not easily degraded by heat (even after being heated, the luminescent properties are not easily deteriorated). The reason is not clear, but it is speculated that in an environment where Ba and Eu coexist, Ba will be preferentially oxidized, and Eu, which is the luminescent center, becomes relatively difficult to oxidize. By appropriately increasing the amount of Ba (z is greater than 0.44), thermal degradation can be fully suppressed. In addition, by not excessive Ba (z is less than 0.99), there is a tendency to easily obtain good luminescent properties while suppressing thermal degradation.

[0044] In addition, the phosphor powder of this embodiment has a tendency that the decrease in luminous intensity in a high temperature environment is relatively small (thermal extinction is suppressed), and the reason for this is not clear, but it is likely related to the suppression of thermal degradation. This means that the phosphor powder of this embodiment can be preferably used for applications with severe temperature changes such as automotive applications.

[0045] The phosphor represented by general formula (I) generally has the general formula Eu 2 Si 5 N 8 The composition represented is that a part of Eu in the phosphor is replaced by M1 (containing at least La) and M2 (containing at least Ba).

[0046] In addition, the phosphor represented by the general formula (I) preferably has the general formula Eu 2 Si 5 N 8 In other words, the phosphor represented by general formula (I) is preferably Eu 2 Si 5 N 8 In the phosphor shown, a part of Eu is replaced by M1 and M2, and a part of Si is replaced by at least Al.

[0047] In the general formula (I), x represents 2 Si 5 N 8 Indicates the degree to which Eu is replaced by M1 in the phosphor.

[0048] In the general formula (I), y represents the degree of substitution of Si by Al.

[0049] In the general formula (I), z represents the degree of substitution of Eu by M2.

[0050] By appropriately adjusting x, y, and z, good fluorescence characteristics can be obtained and the property of being less susceptible to thermal degradation tends to be further improved.

[0051] M1 only needs to contain La. Considering the viewpoint of further improving the luminescence characteristics, among all the elements corresponding to M1, it is preferred that 50 atomic % or more be La, more preferably 70 atomic % or more be La, further preferably 90 atomic % or more be La, and it is particularly preferred that M1 be substantially entirely La.

[0052] M2 only needs to contain Ba. Considering the viewpoint of further improving the luminescence characteristics, among all the elements corresponding to M2, it is preferred that 50 atomic % or more be Ba, more preferably 70 atomic % or more be Ba, further preferably 90 atomic % or more be Ba, and it is particularly preferred that M2 be substantially all Ba.

[0053] x may be 0.005 to 0.2, preferably 0.01 to 0.2, more preferably 0.01 to 0.1, and further preferably 0.02 to 0.07.

[0054] y may be 0 to 0.1, preferably greater than 0 and 0.1 or less, more preferably 0.01 to 0.06, and even more preferably greater than 0.01 and 0.04 or less.

[0055] z may be greater than 0.44 and less than 0.99, preferably greater than 0.44 and less than 0.9, more preferably 0.45 to 0.8, and even more preferably 0.5 to 0.8.

[0056] The composition of the phosphor (the values ​​of x, y, and z) can be determined by ICP emission spectroscopy.

[0057] By properly adjusting the values ​​of x, y and / or z, various properties can be optimized. As one viewpoint, by setting the value of z to 0.8 or less, there is a tendency that thermal degradation is not easy and relatively large luminous intensity is easy to obtain. As another viewpoint, by setting the value of z to 0.5 or more, there is a tendency to further suppress thermal degradation or further suppress thermal extinction.

[0058] In addition, the phosphor represented by the general formula (I) preferably has the general formula Eu 2 Si 5 N 8 One of the reasons for the composition in which a part of Si of the phosphor represented by the general formula is replaced by Al (y is greater than 0) is that the principle of electrical neutrality can be established. Considering the principle of electrical neutrality, for example, it is also possible to consider setting it as follows (i) to (iii). However, considering the fluorescent properties of the obtained phosphor powder, the phosphor represented by the general formula (I) preferably has the general formula Eu 2 Si 5 N 8 The phosphor shown has a composition in which a portion of Si is substituted with Al.

[0059] (i) Al is dissolved in an equimolar amount of La at the Si site (described above). Al is selected because among trivalent cations, the effective ion radius of Al is close to that of Si. It is also possible to use Ga instead of Al.

[0060] (ii) Li is dissolved in the Eu site in an equimolar amount with La. Instead of using Li, it is also possible to use Na, K, or Rb.

[0061] (iii) It is also conceivable to add N in an amount of 1 / 3 of the molar amount of La (N excess) or to add O in an amount of 1 / 2 of the molar amount of La.

[0062] For reference, the general formula Eu 2 Si 5 N 8 The phosphor represented by the general formula (I) is known as the "258 phosphor" based on the numbers representing the composition ratio of each element (see Japanese Patent Publication No. 2010-270196, etc.). As described above, the phosphor represented by the general formula (I) is usually represented by the general formula Eu 2 Si 5 N 8 The fluorophore represented is used as the parent core structure.

[0063] General formula Eu 2 Si 5 N 8 The crystal system of the phosphor represented is an orthorhombic system. According to the literature, the general formula Eu 2 Si 5 N 8 The lattice constants of the phosphor shown are a=0.57094(4)nm, b=0.68207(4)nm, c=0.93291(6)nm and α=γ=β=90.00°. In addition, the lattice volume (a*b*c) is about 0.363nm 3 .

[0064] The lattice constant or lattice volume obtained by X-ray diffraction is a good indicator of the degree of substitution of Ba or the like (reference: Vegard's Law).

[0065] Specifically, in the crystal structure of the phosphor represented by general formula (I), the volume of the unit lattice (lattice volume) is preferably 0.368 nm. 3 Above and less than 0.378nm 3 , more preferably 0.368nm 3 ~0.377nm 3 The phosphor having a lattice volume within the above range has an appropriate degree of substitution with Ba or the like, and tends to obtain good fluorescence characteristics and further improve the property of being less susceptible to thermal degradation.

[0066] Incidentally, the a-axis length of the crystal lattice is preferably 0.574 nm to 0.579 nm, more preferably 0.575 nm to 0.578 nm.

[0067] The b-axis length of the crystal lattice is preferably 0.685 nm to 0.695 nm, and more preferably 0.686 nm to 0.694 nm.

[0068] The c-axis length of the crystal lattice is preferably 0.935 nm to 0.941 nm, and more preferably 0.936 nm to 0.940 nm.

[0069] The property of the phosphor powder of this embodiment that it is not easily degraded by heat can be measured, for example, by the following method: f and I i Calculate the value of I f / I i , and thus quantify it. f / I i It is preferably 0.4 or more, more preferably 0.6 or more, and even more preferably 0.8 or more. f / I i The upper limit of the value of is usually 1.

[0070] The peak intensity of the emission spectrum when the phosphor powder is irradiated with a laser beam having a wavelength of 452 nm at room temperature (typically 23° C.) is defined as I i .

[0071] The peak intensity of the emission spectrum of the phosphor powder when it is irradiated with a laser beam having a wavelength of 452 nm at room temperature after being heated at 200°C for 1 hour and then cooled to room temperature is defined as I f .

[0072] The phosphor powder of this embodiment irradiated with blue light typically emits infrared light (near infrared light). In other words, the phosphor powder of this embodiment is usually a (near) infrared phosphor.

[0073] Quantitatively, when the phosphor powder of the present embodiment is irradiated with laser light having a wavelength of 450 nm, the peak wavelength of the emission spectrum is typically 800 nm or more, specifically 800 nm to 940 nm, and more specifically 800 nm to 900 nm.

[0074] The particle size distribution of the phosphor powder of this embodiment can be appropriately adjusted according to the application of the phosphor powder, desired fluorescence characteristics, and the like.

[0075] The volume-based cumulative 50% particle size (median particle size) D of the phosphor powder of the present embodiment measured by a laser diffraction scattering method is 50For example, it is 0.1 to 50 μm, specifically, it is 0.1 to 10 μm, and more specifically, it is 0.5 to 5 μm.

[0076] The volume-based cumulative 90% particle size D of the phosphor powder of the present embodiment measured by laser diffraction scattering method is 90 For example, it is 1 to 150 μm, specifically, it is 1 to 20 μm, and more specifically, it is 2 to 10 μm.

[0077] The volume-based cumulative 10% particle size D of the phosphor powder of the present embodiment measured by laser diffraction scattering method is 10 For example, it is 0.05 to 10 μm, specifically, it is 0.05 to 5 μm, and more specifically, it is 0.05 to 2 μm.

[0078] <Method for producing phosphor powder>

[0079] The phosphor powder of the present embodiment can be produced, for example, through a series of steps including the following (1) to (3).

[0080] (1) Preparation process of raw material mixed powder

[0081] (2) Calcination process

[0082] (3) Pulverization step of calcined product

[0083] Hereinafter, (1) to (3) will be described in detail.

[0084] (1) Preparation process of raw material mixed powder

[0085] In the raw material mixed powder preparation process, suitable raw material powders are usually fully mixed in a mortar, etc., to obtain the raw material mixed powder. From the viewpoint of avoiding reaction with oxygen and water, the raw material powders are preferably handled and mixed in an inert gas environment such as nitrogen or a rare gas.

[0086] As the raw material powder, nitrides are preferably used. Specifically, LaN, EuN, Ba 3 N 2 、Si 3 N 4 When a phosphor having y greater than 0 (i.e. containing Al) is to be obtained in the general formula (I), it is preferred to further use AlN powder. In addition, the type and amount of the raw material powder may be adjusted in consideration of the elemental composition of the target phosphor.

[0087] The mixing ratio of each raw material powder may be appropriately adjusted to achieve the target composition.

[0088] (2) Calcination process

[0089] In the calcining step, the raw material mixed powder prepared in the step (1) of preparing the raw material mixed powder is filled in an appropriate container and heated using a calcining furnace or the like.

[0090] The calcination temperature is preferably 1400°C to 2000°C, more preferably 1500°C to 1800°C, from the viewpoint of allowing the reaction to proceed sufficiently and from the viewpoint of suppressing the volatilization of components.

[0091] From the viewpoint of allowing the reaction to proceed sufficiently and from the viewpoint of suppressing the volatilization of components, the calcination time is preferably 2 to 24 hours, more preferably 2 to 16 hours.

[0092] The calcination process is preferably carried out in an inert gas environment such as nitrogen. In addition, it is preferred to appropriately adjust the pressure of the calcination environment. Specifically, the pressure of the calcination environment is preferably 0.5 MPa·G or more. When the calcination temperature is high, the phosphor tends to decompose easily, but by making the pressure of the calcination environment high, the decomposition of the phosphor can be suppressed.

[0093] Incidentally, in consideration of industrial productivity, the pressure of the calcination atmosphere is preferably 1 MPa·G or less.

[0094] The container filled with the raw material mixed powder is preferably made of a material that is stable in a high-temperature inert gas environment and does not react with the raw material mixed powder or its reaction product. The material of the container is preferably boron nitride.

[0095] (3) Pulverization step of calcined product

[0096] The calcined product obtained in (2) is usually in a bulk form. Therefore, it is preferred to pulverize the bulk calcined product by mechanically applying force to the calcined product to obtain a powder form.

[0097] The pulverization can be performed using various devices such as a pulverizer, a mortar, a ball mill, a vibration mill, a jet mill, and a stamping mill. The pulverization can also be performed using a combination of two or more of these devices.

[0098] The particle size of the phosphor powder can be adjusted by changing the pulverization conditions.

[0099] The process for producing the phosphor powder of the present embodiment may include any steps other than the above-mentioned (1) to (3).

[0100] As an optional process, for example, an acid treatment process, a classification process, etc. can be cited. By bringing the phosphor powder into contact with an acid, for example, impurities, heterogeneous phases on the surface of phosphor particles (phases that do not contribute to the desired luminescence), etc. can sometimes be removed or reduced. In addition, by using a classification process to remove excessively fine phosphor particles in the phosphor powder, the luminescence characteristics can sometimes be improved. In addition, by using a classification process to remove large phosphor particles in the phosphor powder, a higher quality wavelength converter can sometimes be manufactured.

[0101] <Wavelength converter and light emitting device>

[0102] The wavelength converter of this embodiment contains the above-mentioned phosphor powder.

[0103] The wavelength converter converts light (excitation light) irradiated thereto and emits light having a luminescence peak in a wavelength range different from that of the excitation light.

[0104] The wavelength converter may constitute at least a part of the light emitting device described later.

[0105] The wavelength converter can emit light having a light emission peak in a wavelength range of 600 nm to 900 nm, for example.

[0106] The wavelength converter may or may not contain a phosphor other than the above-mentioned phosphor powder.

[0107] The wavelength converter may be composed of the above-mentioned phosphor powder alone, or may be composed of a base material in which the above-mentioned phosphor powder is dispersed. The base material is not particularly limited, and examples thereof include glass, resin, and inorganic materials.

[0108] The light emitting device of this embodiment has the above-mentioned wavelength converter. The light emitting device can be used for various purposes such as sensing, inspection, analysis, security, optical communication, and medical use. Examples of the light emitting device include LED packages, light sources, spectrophotometers, food analyzers, wearable devices, infrared cameras, moisture measuring devices, and gas detection devices.

[0109] For example, the light emitting device includes a light emitting element and a wavelength converter for converting the wavelength of light emitted from the light emitting element. The shape of the wavelength converter is not particularly limited. As an example, the wavelength converter can be configured in a plate shape. As another example, the wavelength converter can be configured to seal a part of the light emitting element or the entire light emitting surface.

[0110] As the light emitting element, a blue light emitting diode is usually selected.

[0111] The above embodiments of the present invention are described, but these are only examples of the present invention, and various configurations other than the above can be adopted. In addition, the present invention is not limited to the above embodiments, and deformation, improvement, etc. within the scope of achieving the purpose of the present invention are also included in the present invention.

[0112] Example

[0113] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. However, it should be noted that the present invention is not limited to the Examples.

[0114] <Raw materials>

[0115] Prepare the following ingredients.

[0116] LaN: Made by High Purity Chemical Co., Ltd.

[0117] EuN: Made by Pacific Cement Company

[0118] Ba 3 N 2 :Made by Materion, #325mesh

[0119] Si 3 N 4 : Made by Ube Industries, E10 class

[0120] AlN: Made by Tokuyama Co., Ltd., Grade E

[0121] <Manufacturing of phosphor powder>

[0122] Proceed in the following order.

[0123] (1) Mixing of raw materials

[0124] Each raw material was weighed to the mass shown in "Weighing Value" in Table 1, and fully mixed using a mortar to obtain a mixture. These weighing and mixing were performed under a nitrogen atmosphere.

[0125] Table 1 also shows, for reference, the designed composition of each element and the values ​​of x, y, and z in the general formula (I) (assuming that all raw materials react appropriately).

[0126]

[0127] (2) Calcination

[0128] The mixture obtained in (1) was placed in a boron nitride container (container size: 6 mL), and the temperature was raised to 1600° C. at a heating rate of 20° C. / min. The temperature was then maintained at 1600° C. for 4 hours. In this way, a block-shaped calcined product was obtained.

[0129] The calcination environment is as follows.

[0130] Ambient gas: N 2 、Ambient pressure: 0.80MPa·G、Gas introduction temperature: 400℃

[0131] (3) Crushing

[0132] The calcined product obtained in step (2) was crushed using an alumina mortar. Thus, phosphor powder was obtained. The degree of crushing was based on the D 10 , D 50 and D 90 The values ​​in Table 2 described later were adjusted appropriately. In particular, in Examples 4 and 5, the pulverization force was weaker or the pulverization time was shorter than in other Examples and Comparative Examples.

[0133] <Measurement of particle size distribution>

[0134] The particle size distribution was measured using LC13320 (manufactured by Beckman Coulter) by a laser diffraction scattering method in accordance with JIS Z 8825: 2013. The specific procedure is as follows.

[0135] A small amount of phosphor powder was placed in an aqueous solution to which 0.05 wt% sodium hexametaphosphate was added as a dispersant, and the powder was dispersed using a probe-type ultrasonic homogenizer (output 300 W, probe diameter 26 mm) to measure the particle size distribution. D was obtained from the obtained volume frequency particle size distribution curve. 10 , D 50 and D 90 .

[0136] The results are shown in Table 2.

[0137] [Table 2]

[0138] Table 2

[0139]

[0140] <Analysis of composition by ICP emission spectroscopy>

[0141] The composition was analyzed using an Agilent device (model: 5110VDV). Specifically, the analysis was performed in the following procedure.

[0142] First, 10 mg of phosphor powder was placed in a platinum crucible, and 2 g of alkaline flux was added, and the mixture was melted in an electric furnace. After cooling, 20 mL of HCl was added to the platinum crucible, and the mixture was heated and dissolved in a warm bath to obtain a solution. Thereafter, the obtained solution was fixed to 100 mL. The 100 mL solution was diluted 10 times with pure water to obtain a test solution. The test solution was placed in the above-mentioned apparatus, and the composition was analyzed. In addition, based on the analysis results, x, y, and z in the general formula (I) were obtained.

[0143] The analysis results of the composition are shown in Table 3. In Table 3, the values ​​described in "Composition analysis results / mol" are relative molar amounts.

[0144] [Table 3]

[0145] Table 3

[0146]

[0147] <X-ray powder diffraction measurement>

[0148] The XRD pattern of the phosphor powder was obtained using the device Ultima IV of Rigaku. The obtained XRD pattern is shown in Figure 1 .

[0149] By analyzing the obtained spectra using software, it was confirmed that the phosphor powders of Examples 1 to 5 contained orthorhombic crystals of the general formula Eu 2 Si 5 N 8 The fluorophore represented is a fluorophore having a core structure.

[0150] In addition, from the analysis of the obtained XRD pattern, the lattice constants a, b and c, and the lattice volume V were determined. Table 4 shows these values.

[0151] [Table 4]

[0152] Table 4

[0153]

[0154] <Luminescence spectrum measurement>

[0155] Fluorolog-3-iHR-NIR manufactured by HORIBA was used to obtain the emission spectrum when the phosphor powder was irradiated with excitation light of wavelength 450nm (light obtained by monochromatizing continuous wavelength light emitted from a xenon lamp using a diffraction grating). The peak wavelength of the obtained spectrum and the integrated intensity in the wavelength range of 500 to 1400nm were read.

[0156] Table 5 shows the peak wavelength of each phosphor powder and the intensity ratio when the integrated intensity in Comparative Example 1 is set to 1.00.

[0157] [Table 5]

[0158] Table 5

[0159]

[0160] As shown in Table 5, the phosphor powders of Examples 1 to 5 emitted near-infrared light when irradiated with blue light.

[0161] The intensity of the fluorescence emitted from the phosphor powders of Examples 1 to 5 was about the same as that of Comparative Examples 1 and 2. In particular, the intensity of the fluorescence emitted from the phosphor powders of Examples 1 and 2 was not inferior to that of Comparative Examples 1 and 2.

[0162] <Evaluation of Thermal Deterioration>

[0163] An upright microscope manufactured by Olympus, a multi-channel spectrometer MCPD-98003095 manufactured by Otsuka Electronics, a blue laser source (peak wavelength 452nm) manufactured by Sawaki Kobo, and a temperature characteristics evaluation stage HFS600 (equipped with a heater for heating and a water cooling mechanism for cooling) manufactured by Linkam were combined to assemble a device capable of evaluating the luminescence of a single particle of a phosphor.

[0164] Using this device, the degree of thermal degradation was evaluated in the following order (1) to (5).

[0165] (1) A quartz petri dish containing 0.1 g of phosphor powder was placed on the evaluation stage.

[0166] (2) The phosphor powder was irradiated with a blue laser at room temperature (23° C.) and the emission spectrum was measured. The peak intensity (maximum value of the spectrum) of the obtained emission spectrum was defined as I i .

[0167] (3) The phosphor powder was heated from room temperature at a rate of 100° C. / min using a heating heater and maintained at 200° C. for 1 hour.

[0168] (4) Turn off the heating heater and cool the phosphor powder using a water cooling mechanism. After about 1 hour, irradiate the phosphor powder cooled to room temperature with a blue laser and measure the luminescence spectrum. The peak intensity (maximum value of the spectrum) of the obtained luminescence spectrum is set as I f .

[0169] (5) Calculate I f / I i The value of is taken as an indicator of thermal degradation.

[0170] The results are shown in Table 6.

[0171] Table 6

[0172] Sample name <![CDATA[I f / I i ]]> Example 1 089 Example 2 0.96 Example 3 0.96 Example 4 0.97 Example 5 098 Comparative Example 1 0.35 Comparative Example 2 0.77

[0173] As shown in Table 6, the phosphor powders of Examples 1 to 5 (containing phosphors having z greater than 0.44 and not more than 0.99 in the general formula (I)) were less thermally degraded than the phosphor powders of Comparative Examples 1 and 2 (having z not more than 0.44 in the general formula (I)). In particular, the phosphor powders of Examples 2 and 3 containing phosphors having a relatively large z (large Ba substitution ratio) were less thermally degraded.

[0174] <Evaluation of Thermal Extinction>

[0175] In (3) of the above-mentioned <Evaluation of Thermal Deterioration>, after the phosphor powder has been heated to 200°C for 10 minutes, the phosphor powder is irradiated with a blue laser and the emission spectrum is measured. The peak intensity (maximum value of the spectrum) of the obtained emission spectrum is defined as I'. I' / I i The value of is taken as an indicator of thermal extinction.

[0176] The results are shown in Table 7.

[0177] [Table 7]

[0178] Table 7

[0179] Sample name <![CDATA[I′ / I i ]]> Example 1 0.22 Example 2 0.41 Example 3 0.45 Example 4 0.41 Example 5 0.38 Comparative Example 1 0.09 Comparative Example 2 0.17

[0180] As shown in Table 7, the phosphor powders of Examples 1 to 5 (containing phosphors having z greater than 0.44 and less than 0.99 in the general formula (I)) are less susceptible to thermal extinction than the phosphor powders of Comparative Examples 1 and 2 (having z less than 0.44 in the general formula (I)). In particular, the phosphor powders of Examples 2 and 3 containing phosphors having a relatively large z (large Ba substitution ratio) are less susceptible to thermal extinction.

[0181] This application claims priority based on Japanese patent application No. 2021-032318 filed on March 2, 2021, the disclosure of which is incorporated herein in its entirety.

Claims

1. A phosphor powder comprising a phosphor represented by the following general formula (I), <h2 style=";text-align:left;direction:ltr">(Eu<h2 style=";text-align:left;direction:ltr"> (1-x)(1-z) <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> (1-x)z <h2 style=";text-align:left;direction:ltr"> )2(Si<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )5N8···(I) In the general formula (I), M1 is La, or contains La and one or more elements selected from lanthanoid elements other than Y and La, M2 is Ba, or contains Ba and one or more elements selected from Mg, Ca and Sr, x is 0.005 to 0.2, y is greater than 0 and less than 0.1, z is greater than 0.44 and less than or equal to 0.

99.

2. The phosphor powder according to claim 1, wherein In the crystal structure of the phosphor, the volume of the unit cell is 0.368 nm 3 Above and less than 0.378nm 3 .

3. The phosphor powder according to claim 1 or 2, wherein The peak intensity of the emission spectrum when the phosphor powder is irradiated with a laser of wavelength 452 nm at room temperature is defined as I i , The peak intensity of the emission spectrum of the phosphor powder obtained by heating the phosphor powder at 200° C. for 1 hour and then cooling to room temperature when irradiating the phosphor powder with a laser having a wavelength of 452 nm is defined as I f hour, I f / I i The value of is 0.4 or more.

4. The phosphor powder according to claim 1 or 2, wherein When the phosphor powder is irradiated with light having a wavelength of 450 nm, the peak wavelength of the emission spectrum is 800 nm or longer. 5 . A wavelength converter comprising the phosphor powder according to claim 1 . 6 . A light emitting device comprising the wavelength converter according to claim 5 .

Citation Information

Patent Citations

  • Phosphor, method for manufacturing phosphor, phosphor-containing composition, light-emitting device, lighting apparatus, image display, and fluorescent paint

    JP2010270196A

  • Hydraulic system of construction machine

    JP2021032318A

  • Light-emitting device

    WO2019240150A1

  • Phosphor, method for producing same and light emitting element

    WO2020203234A1

  • Silica-based nitride red fluorescent powder and preparation method thereof

    CN101831295A